2007
DOI: 10.1111/j.1365-2486.2007.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate increases regional tree‐growth variability in Iberian pine forests

Abstract: Tree populations located at the geographical distribution limit of the species may provide valuable information about tree-growth response to changes on climatic conditions. We established nine Pinus nigra, 12 P. sylvestris and 17 P. uncinata tree-ring width chronologies along the eastern and northern Iberian Peninsula, where these species are found at the edge of their natural range. Tree-growth variability was analyzed using principal component analysis (PCA) for the period 1885-1992. Despite the diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
209
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(262 citation statements)
references
References 36 publications
41
209
2
10
Order By: Relevance
“…The increasing negative (positive) relationship with the mean temperature of spring-summer months (autumn to spring precipitation) (Fig. 7) suggests that moisture stress has increased in all regions, in accordance with results for most of the Mediterranean (Andreu et al, 2007;Macias et al, 2006;Piovesan et al, 2008) and parts of North America (Biondi, 2000). The significant upward trend of the mean sensitivity of tree-ring chronologies (Fig.…”
Section: Relationship Between Climate and Radial Growthsupporting
confidence: 85%
See 1 more Smart Citation
“…The increasing negative (positive) relationship with the mean temperature of spring-summer months (autumn to spring precipitation) (Fig. 7) suggests that moisture stress has increased in all regions, in accordance with results for most of the Mediterranean (Andreu et al, 2007;Macias et al, 2006;Piovesan et al, 2008) and parts of North America (Biondi, 2000). The significant upward trend of the mean sensitivity of tree-ring chronologies (Fig.…”
Section: Relationship Between Climate and Radial Growthsupporting
confidence: 85%
“…In the Iberian Peninsula, black pine is distributed along the eastern mountain ranges and covers a wide latitudinal gradient. These forests have been greatly affected by climate change during the second half of 20th century (Andreu et al, 2007). These facts place black pine in an intermediate position between boreal locations, in which mainly positive growth trends have been detected (Martínez-Vilalta et al, 2008), and more xeric pines, where negative trends dominate (Sarris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although this is usual in arid regions (i.e. Mediterranean region) (Rozas 2001;Andreu et al 2007), similar effects have recently been observed also for trees growing in boreal regions (Wilmking et al 2004). Thus, knowledge on climate growth relationships, considering regional variability (Andreu et al 2007), is necessary.…”
Section: Introductionsupporting
confidence: 67%
“…Andreu et al, 2007;Cherubini et al, 2003) and physiological mechanisms linked to tree growth (e.g. Montgomery, 2004;Pereira, 1994) the causes and community-level consequences of interspecific variation in tree growth remain poorly understood, even for many canopy dominant species.…”
Section: Introductionmentioning
confidence: 99%